Pendampingan Masyarakat Nelayan Pulau Tunda Pada Kegiatan Pemulihan Ekonomi dan Sosial Pasca Pandemi Covid-19 - sastra wijaya; Ika Evitasari Aris (Universitas Mathla'ul Anwar Banten, 2022)
ASSISTANCE OF THE TUNDA ISLAND FISHING COMMUNITY IN ECONOMIC AND SOCIAL RECOVERY ACTIVITIES POST COVID-19 PANDEMIC During The Covid-19 Pandemic, The Economic And Social Conditions Of The Delayed Community Were Indeed Very Well Known, Especially In Areas Located On Small Islands, Increasingly Developing These Conditions, Therefore Intervention From Various Parties Was Needed To Be Able To Stimulate These Conditions So That Economic And Social Activities Could Immediately Rise. Back on the island of delay even though it is in new normal condition. Community service activities involving as many as 320 students and 17 lecture in primagraha universities are expected to be able to take advantage of the restoration of the economic and social conditions of the tunda island community or sara village residents, tirtayasa district, serang regency, through this activity it is also expected to further encourage the tourism sector on tunda island to be better known in the community. The number of tourist visits during the covid-19 pandemic has decreased by 60%. The development of adequate education and health facilities by the local government will greatly assist the tunda island community in increasing their tourism potential with a holistic approach. Development based on the habits, culture and customs of the community will have an impact on the economic and social conditions of the tunda island community. Tunda island or the village of sara residents, which has extraordinary natural beauty and marine resources, can be trusted by the local government to be a leading destination that can have an impact on improving the economic and social conditions of the community, which in turn will also have an impact on the potential for improving the economic and social conditions of the community. Local revenue in the tourism sector. Tunda island tourism promotion through digital will be able to better introduce the beauty of marine resources owned by domestic tourists and national tourists.